Chemical, Physical and Sensory Characteristics of Cookies Substituted with Shiitake Mushroom Powder (Lentinula edodes) - Wardah; Sihmawati, Rini Rahayu (International Conference of Innovation and Community Engagement, 2024)
Shiitake mushrooms (Lentinula edodes) are well known as a food source with numerous health benefits, mainly due to their protein and fiber content, which support bodily functions. These mushrooms also contain various phytochemicals, including secondary metabolites and antioxidants. Some of the secondary metabolites found in shiitake mushrooms include alkaloids, flavonoids, steroids, terpenoids, saponins, polysaccharides, tannins, vitamin C, vitamin D, and lipids. Additionally, shiitake mushrooms possess anticancer, anti-inflammatory, antioxidant, antibacterial properties, and can enhance the immune system. Compounds such as eritadenine, sterols, and beta-glucans present in shiitake mushrooms play a role in lowering cholesterol levels. Given their rich nutritional profile, shiitake mushrooms have the potential to be used as a partial substitute for wheat flour in cookie production, especially for products aimed at pregnant women.This study aims to evaluate the effect of substituting shiitake mushroom flour on the nutritional content, including vitamin C, vitamin D, folic acid, and protein, as well as on the texture and sensory preferences of the cookies. Various proportions of wheat flour substituted with shiitake mushroom flour were tested, and the results showed that a 30% substitution of shiitake mushroom flour produced cookies with 5.13 mg/100 g of vitamin C, 1.26 IU/100 g of vitamin D, 193.964 µg/100 g of folic acid, 7.256 g/100 g of protein, and a crisper texture, averaging 36.98 mm/50 g/10 s. The higher the percentage of shiitake mushroom flour used, the higher the content of vitamin C, vitamin D, folic acid, protein, and the crispness of the cookies. Panelists preferred the color of cookies with 15% and 22.5% shiitake mushroom flour substitution, while the best aroma and flavor were found in cookies with 15% substitution. The study concludes that shiitake mushrooms have the potential to be used as a natural additive that can enhance the nutritional value and crispness of cookies without compromising sensory quality, making them suitable for development as healthier food products.